Nucleotide sequences of the nucleocapsid (NP) gene of a Malaysian velogenic Newcastle disease virus strain AF2240 - Yusoff, Khatijah; Tan, Wen Siang; Kho, Chiew Ling (2005)
The present invention relates to nucleotide sequences encoding the nucleocapsid (NP) protein and phosphoprotein (P) of Newcastle disease virus (NDV) and the production of the corresponding proteins with recombinant plasmids bearing the nucleotide sequences in Escherichia coli.